PENGARUH INOVASI PRODUK, ORIENTASI KEWIRAUSAHAAN DAN KEMAMPUAN MENGINDERA PASAR TERHADAP OMZET PENJUALAN ONLINE PADA USAHA MIKRO KECIL MENENGAH (UMKM) DI KABUPATEN POLEWALI MANDAR - Ratu Chakti, Andi Gunawan; Saleh, Nursahdi (Clavia, 2021)
This study aims to determine the effect of Product Innovation, Entrepreneurship Orientation and Market Sensing Ability individually (partial) and together (simultaneously) on online sales turnover in Micro, Small and Medium Enterprises (MSMEs) in Polewali Mandar Regency. This research approach uses a survey. The research was conducted on employees of Micro, Small and Medium Enterprises (MSMEs) in Polewali Mandar Regency. The time of the research was carried out from September to December 2021. The population used in this study was small industrial entrepreneurs within Polman Regency, which operated 55 people. The sample was determined by the simple random sampling technique. Data analysis used multiple regression analysis (multiple regression analysis). The results show that Product Innovation, Entrepreneurship Orientation, and Market Sensing Ability individually (partial) and simultaneously (simultaneously) have a positive and significant impact on online sales turnover in Micro, Small and Medium Enterprises (MSMEs) in Polewali Mandar Regency. MSME owners who are the object of research are Micro, Small and Medium Business Owners who do marketing and sales through internet media, either using Marketplace, Social Media or Whatsapp. Every MSME experienced an increase in sales turnover through online, so it can be said that the owner has good business performance in carrying out business activities.